Study of Public Transport Development in South Bali Districts: Potential Public Transport Mode - Putri, Adni; Farda, Muhammad; Santosa, Sigit; Dirgahayani, Puspita; Suthanaya, Putu; Andani, I Gusti; Sutanto, Hansen; Charky, Laily; Nurjanah, Nunuj (Unijourn Publisher, 2021)
Bali Province in Indonesia is one of the most attractive tourist destinations in the world. The number of tourists visiting this province keeps increasing year by year parallel with the increase of the population of local citizens. Such a phenomenon will certainly increase travel demand and put pressure on the current transport infrastructure. Hence, transport infrastructure development is essential to support the travel demand. This study explores the possibility of implementing a new public transport system in the South Bali District, a district with numerous tourist attractions and activity centres. Data collection on the current transport system and land use in the district were carried out to understand potential corridors for public transport. A stated preference survey was also conducted to discover the public transport mode preferred by the respondents, encompassing tourists and local citizens. This study then recommends the type of public transport mode to be implemented in the district based on i) space availability, ii) respondent preference, and iii) ability to accommodate demand based on calculation. The study concludes that Automated Rapid Transit (ART) is a mode that has the highest potential to be implemented in South Bali Districts.